Kontribusi Divisi Pembelian dalam Manajemen dan Pengendalian Persediaan Bahan Baku di Restoran Over Horizon, Semarang - Dewi, Maria Refita (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2025)
Effective raw material management is a crucial aspect of the restaurant industry to ensure the availability of products in the right quantity and quality while enhancing operational efficiency. The purchasing division plays a strategic role in planning, coordinating, and controlling the procurement process to ensure smooth restaurant operations. This study aims to analyze the role of the purchasing division in managing and controlling raw material inventory at Over Horizon Restaurant. This research adopts a qualitative approach using the case study method. Data collection was conducted through in-depth interviews with purchasing staff and direct observations of the procurement and inventory management processes in the restaurant. The findings indicate that the purchasing division plays a significant role in ensuring the timely and efficient availability of raw materials. Key activities include daily recording and monitoring, as well as effective coordination with other divisions to determine procurement needs. Additionally, strong interdepartmental communication contributes significantly to enhancing the restaurant's operational efficiency. In conclusion, the purchasing division at Over Horizon Restaurant has effectively fulfilled its role in managing and controlling raw materials. As an implication, this study suggests the development of a more adaptive and integrated raw material management system to address the evolving challenges in the restaurant industry.